2020
DOI: 10.1371/journal.pone.0228225
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of atoh1 genes in the lower rhombic lip during hindbrain morphogenesis

Abstract: The Lower Rhombic Lip (LRL) is a transient neuroepithelial structure of the dorsal hindbrain, which expands from r2 to r7, and gives rise to deep nuclei of the brainstem, such as the vestibular and auditory nuclei and most posteriorly the precerebellar nuclei. Although there is information about the contribution of specific proneural-progenitor populations to specific deep nuclei, and the distinct rhombomeric contribution, little is known about how progenitor cells from the LRL behave during neurogenesis and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…As shown in Fig. 2, the NDD dramatically increased during this time period, consistent with previous qualitative descriptions (Belzunce et al, 2020; Lyons et al, 2003; Voltes et al, 2019). Only few cells underwent differentiation before 24 hpf (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 2, the NDD dramatically increased during this time period, consistent with previous qualitative descriptions (Belzunce et al, 2020; Lyons et al, 2003; Voltes et al, 2019). Only few cells underwent differentiation before 24 hpf (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Here, we made use of the zebrafish embryonic brainstem—the hindbrain, which undergoes a segmentation process along the anteroposterior (AP) axis leading to the formation of seven metamers called rhombomeres (Fraser et al, 1990; Jimenez-Guri and Pujades, 2011; Jimenez-Guri et al, 2010; Kiecker and Lumsden, 2005; Pujades, 2020). The first neuronal differentiation events in the hindbrain are observed just prior to 24 hours post-fertilization (hpf), with a pronounced increase of events from 30 hpf onwards, concomitant with dramatic morphogenetic changes (Belzunce et al, 2020). Neuronal differentiation in the hindbrain needs to be finely tuned, as it involves changes in proliferative capacity, an extraordinary displacement of neurons from their birth site and complex tissue morphogenetic movements over time.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, we observed that boundary cells were devoid of Notch-activity at early stages (Figure 2D, and inserts; see mCherry cells with no GFP expression in (d)). In contrast, the rhombic lip and the rhombomeric territories were Notch-active (Figures 2D and S3A; Belzunce et al, 2020). However, by 48 hpf, most of the boundary progenitor cells were Notch-active (Figure 2E, and inserts; see in (e) transverse views and corresponding inserts, showing that most of the dorsal mCherry cells facing the ventricle expressed GFP).…”
Section: Resultsmentioning
confidence: 98%
“…The Tg[HuC:GFP] line labels differentiated neurons (Park et al, 2000). Tg[atoh1a:GFP] (Belzunce et al, 2020) labeling the rhombic lip was generated by crossing Tg[atoh1a:KalTA4] (Distel et al, 2009) and Tg[UAS:GFP].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation